2012
DOI: 10.1016/j.biomaterials.2012.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-inspired silver-releasing antibacterial hydrogels

Abstract: A silver-releasing antibacterial hydrogel was developed that simultaneously allowed for silver nanoparticle formation and gel curing. Water-soluble polyethylene glycol (PEG) polymers were synthesized that contain reactive catechol moieties, inspired by mussel adhesive proteins, where the catechol containing amino acid 3,4-dihydroxyphenylalanine (DOPA) plays an important role in the ability of the mussel to adhere to almost any surface in an aqueous environment. We utilized silver nitrate to oxidize polymer cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
178
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(189 citation statements)
references
References 32 publications
5
178
1
Order By: Relevance
“…These results contradict prevalent theories that mussels remain attached due to robust strength in their adhesive plaque structures (see below figure), which have inspired biomimetic approaches for designing antibacterial hydrogels and tissue adhesives with similar functionality 51 . In contrast, these new findings can serve to inform bioinspired dynamic loading designs based on clever material distribution that overcome trade-offs among energy dissipation and deformation, such as earthquake-resistant structures.…”
Section: Passive and Active Mechanofunctional Materialscontrasting
confidence: 55%
See 1 more Smart Citation
“…These results contradict prevalent theories that mussels remain attached due to robust strength in their adhesive plaque structures (see below figure), which have inspired biomimetic approaches for designing antibacterial hydrogels and tissue adhesives with similar functionality 51 . In contrast, these new findings can serve to inform bioinspired dynamic loading designs based on clever material distribution that overcome trade-offs among energy dissipation and deformation, such as earthquake-resistant structures.…”
Section: Passive and Active Mechanofunctional Materialscontrasting
confidence: 55%
“…Recent efforts in realizing synthetic bio-based technologies have led to many successes in mimicking passive material properties that require no energy expenditures, such as adhesion 51 , elasticity 17 , strength and toughness 52 , self-healing 53 and stimuli responsiveness 54 . In addition, many active, biomimetic systems that do utilize energy to carry out their mechanical functions have also been produced, including synthetic bio-actuators 55 , contractile polymers 56 and electrospun climbing fibres 56 .…”
Section: Passive and Active Mechanofunctional Materialsmentioning
confidence: 99%
“…Hence, much attention has shifted to what the natural world has to offer by reverse-engineering bio-inspired antibacterial surface solutions. [13][14][15] It is within the context of natural antibacterial surfaces that the presence of nanopillar surface structures on Psaltoda claripennis cicada wings was identified as having bactericidal properties against Gram-negative bacteria, which was attributed to a purely physical mechanism and not by any chemical attributes. 16 This was demonstrated by coating the cicada wings with a layer of gold and performing repeat cell studies; here it was shown that these chemically inert nanopillars also provided a bactericidal effect.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond that, specific peptide sequences can feature anti-microbial activity (Peyre et al, 2012;Krizsan et al, 2014). Classic and novel antibiotic reagents are mostly used through a release mechanism to circumvent infections of biomaterials (Fullenkamp et al, 2012;Lee et al, 2015).…”
Section: Components Of Multifunctional Biomaterials Coatingsmentioning
confidence: 99%